The Foreign Exchange Market With the Cryptocurrency and "Kimchi Premium" - Jeong Hun Oh (International Telecommunications Society (ITS), 2018)
This paper explores the remarkable roles of exchange rates when a cryptocurrency is adopted and commonly used as another type of foreign currency in the international economy. First, in order to examine its movement, we describe the price of a cryptocurrency as the relative price in terms of a standard currency using the exchange rate formula. Second, we identify three determinants of the "Kimchi premium" from the equilibrium condition in the foreign exchange market: the gaps in the rates of return of the cryptocurrency, the interest rates of the standard currencies, and the expected cryptocurrency exchange rates. Finally, using the money market and the foreign exchange market rationalities, we demonstrate the process that the new cryptocurrency in a country can cause a rise in the money supply, a fall in the interest rate, and a rise in the exchange rate in the end.
Keywords: 330; Cryptocurrency; "Kimchi premium; " Exchange rate; Interest Rate